2022
DOI: 10.1155/2022/5374419
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Lymphocyte and Neutrophil-Lymphocyte Ratio for Prediction of Hospital Outcomes in Patients with Abdominal Trauma

Abstract: Background. The platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR) reflect the patient inflammatory and immunity status. We investigated the role of on-admission PLR and NLR in predicting massive transfusion protocol (MTP) activation and mortality following abdominal trauma. Methods. A 4-year retrospective analysis of all adult abdominal trauma patients was conducted. Patients were classified into survivors and nonsurvivors and low vs. high PLR. The discriminatory power for PLR and NLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The neutrophil/lymphocyte ratio and monocyte/high-density lipoprotein cholesterol ratio trend to an elevated level in non-surviving patients with sepsis, and evaluation of the neutrophil/lymphocyte ratio together with monocyte/high-density lipoprotein cholesterol ratio is an independent risk factor for increased mortality ( 25 ). In abdominal trauma patients, on-admission platelet/lymphocyte ratio but not neutrophil/lymphocyte ratio helps early risk stratification and timely management and predicts mortality ( 26 ). Abnormal CD4+ and CD8+ T cell responses are major components of a dysregulated acquired immune response, and the immune dysfunction of Tregs also contributes to pathogenesis ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil/lymphocyte ratio and monocyte/high-density lipoprotein cholesterol ratio trend to an elevated level in non-surviving patients with sepsis, and evaluation of the neutrophil/lymphocyte ratio together with monocyte/high-density lipoprotein cholesterol ratio is an independent risk factor for increased mortality ( 25 ). In abdominal trauma patients, on-admission platelet/lymphocyte ratio but not neutrophil/lymphocyte ratio helps early risk stratification and timely management and predicts mortality ( 26 ). Abnormal CD4+ and CD8+ T cell responses are major components of a dysregulated acquired immune response, and the immune dysfunction of Tregs also contributes to pathogenesis ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under severe trauma, the deactivation of monocytes is correlated with the injury severity of the patients [ 30 ], leading to immunocompetence of the cells with a profound loss of antigen-presenting ability [ 31 ]. However, although MLR, NLR, and PLR have been implicated as useful biomarkers for trauma patients in some studies [ 32 , 33 , 34 , 35 ], this study of propensity score-matched patient populations with polytrauma revealed that there was no significant difference in the counts of monocytes, neutrophils, and platelets, as well as in MLR, NLR, and PLR between patients who died and survived. In contrast, patients who died had a significantly higher lymphocyte count than the survivors.…”
Section: Discussionmentioning
confidence: 61%
“…The neutrophil-to-lymphocyte ratio (NLR) combines information on neutrophils and lymphocytes and is less affected than other indices by physiological factors, specimen handling and other factors; it is also inexpensive and easy to obtain and produces relatively stable results. Recently, many studies confirmed the association between this indicator and multiple diseases, including acute coronary syndrome, cancer, and neuromyelitis optica spectrum disorder, and showed that the NLR has high clinical application value [ 7 10 ]. Relevant studies have found that the NLR may be an independent predictor of unfavorable prognosis and early death in patients with acute cerebral infarction [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%